New threats to the subscription model - Koenigsberg, Oded, 1964- (MIT Sloan Management Review, 2023)
Proponents of the subscription model argue that it offers customers a better user experience and a lower barrier to access, while providers gain predictability and ease of communication with customers. But the risks of supply chain disruption and inflation are calling into question vendors’ ability to fulfill their service commitments to customers — and retain them — over the long term.